Risk Prioritization from the Crowd-Shipping Provider's Perspective using the CIMAS Method - Švadlenka, Libor; Bajec, Patricija; Pivtorak, Halyna; Bošković, Sara; Jovčić, Stefan; Dobrodolac, Momčilo (Scientific Oasis doo Belgrade, 2024)
Crowd-shipping presents a new trend in shipment distribution. It is a process in which the crowd is employed to deliver the items. Effective risk prioritization is essential in city logistics and delivery, especially with the emergence of crowd-shipping. As crowd-shipping platforms grow, they bring uncertainties and challenges that can significantly impact operational efficiency and customer confidence. Emphasizing risk prioritization is crucial for many reasons, including trust and security, improving operational efficiency, and ensuring regulatory readiness. Risk prioritization is more than a mere formality; it is a vital element in successfully managing the intricacies of crowd-shipping. By methodically addressing and mitigating risks, providers can strengthen their operational capabilities, foster better customer connections, and ultimately promote the sustainable advancement of crowd-shipping services. This paper prioritizes the risks in crowd-shipping from the crowd-shipping provider’s perspective, using an MCDM approach such as CIMAS. The risks are prioritized in descending order. Comparative analysis with the BWM indicates the high reliability of the results obtained by the CIMAS method.
Stanovení priority rizik z pohledu poskytovatele hromadné dopravy pomocí metody CIMAS
Keywords: Risk; Prioritization; Crowd-Shipping; CIMAS Method; Rizika; prioritizace; crowd-shipping; metoda CIMAS